Development of vaccines against Crimean-Congo haemorrhagic fever virus. Issue 44 (20th October 2017) - Dowall, Stuart D.; Carroll, Miles W.; Hewson, Roger
Abstract: Crimean-Congo haemorrhagic fever virus (CCHFV) is a deadly human pathogen of the utmost seriousness being highly lethal causing devastating disease symptoms that result in intense and prolonged suffering to those infected. During the past 40 years, this virus has repeatedly caused sporadic outbreaks responsible for relatively low numbers of human casualties, but with an alarming fatality rate of up to 80% in clinically infected patients. CCHFV is transmitted to humans by Hyalomma ticks and contact with the blood of viremic livestock, additionally cases of human-to-human transmission are not uncommon in nosocomial settings. The incidence of CCHF closely matches the geographical range of permissive ticks, which are widespread throughout Africa, Asia, the Middle East and Europe. As such, CCHFV is the most widespread tick-borne virus on earth. It is a concern that recent data shows the geographic distribution of Hyalomma ticks is expanding. Migratory birds are also disseminating Hyalomma ticks into more northerly parts of Europe thus potentially exposing naïve human populations to CCHFV. The virus has been imported into the UK on two occasions in the last five years with the first fatal case being confirmed in 2012. A licensed vaccine to CCHF is not available. In this review, we discuss the background and complications surrounding this limitation and examine the current status and recent advances in the development of vaccines against CCHFV.